Rapid weight loss across combat sports and the relationships between methods and magnitude - Barley, O. R.; Harms, C. A. (Translational Sports Medicine, 2025)
This study examined rapid weight loss (RWL) habits across combat sports (CS) and how common usage of different methods was related to the magnitude of RWL. Competitors (N = 256) from CS including boxing, Brazilian jiu-jitsu, muay thai/kickboxing (MT/KB), wrestling, mixed martial arts (MMA), judo, taekwondo, and karate participated in the study. Athletes completed an online survey which included questions on their regular weight loss habits, including magnitudes of weight loss over different time periods and types of methods utilised. Athletes typically started losing weight in their early 20s and engaged in RWL on average three times a year. Magnitudes of weight loss were greater in MT/KB and MMA than other cCS examined (d between 0.63 and 1.54). Wrestlers demonstrated higher prevalence of skipping meals or fasting than other CS (d between 0.7 and 1.29). Athletes at higher competitive levels engaged in larger magnitudes of RWL (d between 0.49 and 0.57). The usage of methods of body fluid manipulation such as fluid restriction, water loading, and sauna were associated with greater amounts of weight loss within 2 weeks and 24 h of weighing in (d between 0.36 and 0.45). Findings indicate that larger weight cuts are linked to strategies involving higher risk, such as sauna, and may be more common among athletes who begin RWL practices at a younger age. Use of certain high-risk methods were associated with increased likelihood of disordered eating behaviours. To reduce reliance on these practices, practitioners and regulators should emphasise the use of smaller weight cuts and to begin losing weight further out from competition.